Cover Jurnal Fitopatologi Vol. 17 No. 4, Juli 2021 (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology, JFI Vol. 17 No. 4, July 2021.